Socioeconomic inequalities in childhood and adolescent obesity in Australia: The role of behavioral and biological factors - Nirmal Gautam; Aquib Chowdhury; Mohammad Mafizur Rahman; Rasheda Khanam (PLoS ONE, 2025)
Background Obesity among children and adolescents is a significant public health concern, influenced by a complex interplay of biological and behavioral factors. However, the extent to which these factors contribute to socioeconomic disparities in obesity remains inadequately understood. Therefore, this study aimed to elucidate the roles of behavioral factors —such as dietary habits, physical activity levels, and outdoor activities—alongside biological factors, including parental body weight, in shaping socioeconomic inequalities in obesity among Australian children and adolescents. Methods This study utilized data from the Birth Cohort (n=5101) and Kindergarten Cohort (n=4983) of the Longitudinal Study of Australian Children (LSAC). LSAC data have been collected biannually since 2004 for the B cohort and since 2000 for the K cohort. The study employed Concentration Index and Decomposition Index analyses to assess the magnitude and to identify the relative contributions of socioeconomic inequalities in obesity, focusing on the contributions of behavioral and biological factors. Results The analysis revealed that socioeconomic disparities in obesity among children and adolescents were significantly influenced by both biological and behavioral factors, as well as household income. Biological factors were found to account for 28.96% of these disparities, while household income contributed 49.17%, and behavioral factors explained 10.36% of the inequalities. Moreover, non-consumption of fatty foods and outdoor activities were found to be associated with a decrease in obesity by β:−0.317, β:−0.084, respectively. However, non-consumption of fruits and vegetables and maternal BMI were significantly correlated with an increased risk of obesity in children (β:0.406) and adolescents (β:0.117) respectively. Conclusion These findings provide critical insights into the distribution of obesity across different socioeconomic groups in Australia, highlighting the substantial role of household income and the combined impact of biological and behavioral factors. The results emphasize the importance of developing targeted public health interventions that support families from lower socioeconomic backgrounds to reduce obesity-related disparities.